Construction of Wife's Permit on Polygamy Practice of Tablig Pilgrim's Mayangan Jogoroto Jombang - Fageh, Achmad; Najah, Ahmadun (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2022)
The focus of this study is the construction of the wife's license to practice polygamy on Tablig Mayangan Jombang Pilgrims. The purpose of the study is to find out the practice of polygamy Of Tablig Mayangan Pilgrims and the model of the wife's license to practice polygamy Tablig Pilgrims Mayangan. This type of field research is qualitative, using the analysis of normative legal and sociological approaches, with inductive reasoning and Data collection techniques using observation, documentation, and interviews. The results showed that polygamous behavior carried out by Tablig pilgrims is based on rational and sharia-laden aspects because polygamous behavior arises due to consideration of the struggle of da'wah as Tablig pilgrims. Polygamy is also considered worship for the husband and wife of Tablig worshippers. Therefore, the practice of polygamy of the husbands and husbands of Tablig pilgrims strictly follows the provisions stipulated in Law No.1 of 1974, article 4 paragraph 2 about committing the cause of polygamous marriage by obtaining the wife's permission. The construction model of the wife's license to practice polygamy Tablig pilgrims is the model of Wira'i, which considers prudence over the property of the third wife as a rich man to avoid disputes over the seizure of Gono-Gini property and so on. [Fokus penelitian ini adalah kontstruksi izin istri dalam praktik poligami pada Tablig Pilgrims Mayangan Jombang. Tujuan penelitian ini untuk mengetahui perilaku poligami Tablig Pilgrims Mayangan dan model izin istri dalam praktik poligami Tablig Pilgrims Mayangan. Jenis penelitian ini adalah penelitian kualitaltif dengan menggunakan analisis normatif hukum dan sosiologis dengan penalaran induktif. Teknik pengumpulan data menggunakan observasi, dokumentasi dan wawancara. Hasil penelitian menunjukkan bahwa Perilaku poligami yang dilakukan Tablig Pilgrims didasari oleh aspek yang rasional dan sesuai syariat Islam, sebab perilaku poligami timbul karena pertimbangan perjuangan dakwah selaku anggota Tablig Pilgrims. Poligami juga dianggap sebagai ibadah bagi suami istri Tablig Pilgrims. Oleh karena itu, Praktik poligami suami-suami Tablig Pilgrims betul betul mengikuti ketentuan yang telah ditetapkan dalam Undang - Undang No.1 Tahun 1974 pasal 4 ayat 2 tentang keharusan poligami dengan mendapatkan izin istri. Model konstruksi izin istri dalam praktik poligami Tablig Pilgrims, berdasarkan kasus yang diteliti adalah model wirā’i, yakni atas pertimbangan kehati-hatian terhadap harta istri ketiga sebagai orang yang kaya raya, agar terhindar dari sengketa perebutan harta gono - gini dan sebagainya.]